2021
DOI: 10.1186/s12951-021-01002-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of cell-penetrating peptides with nanomaterials for the potential therapeutics of central nervous system disorders: a review

Abstract: Although nanomedicine have greatly developed and human life span has been extended, we have witnessed the soared incidence of central nervous system (CNS) diseases including neurodegenerative diseases (Alzheimer’s disease, Parkinson’s disease), ischemic stroke, and brain tumors, which have severely damaged the quality of life and greatly increased the economic and social burdens. Moreover, partial small molecule drugs and almost all large molecule drugs (such as recombinant protein, therapeutic antibody, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 199 publications
0
37
0
Order By: Relevance
“…The peptides were primarily selected on the basis of predicted relatively higher blood brain barrier score, lower haemolytic activity and toxicity (Table 1). Among amphipathic peptides, we selected well-characterized and widely used pVEC, ARF, MAP and TP-10 while TAT, R8, IMT-P8, SynB3 and Penetratin were selected from the cationic class (Stalmans et al, 2015; Zhang et al, 2021). Peptides from the hydrophobic class were not selected due to their limited solubility and high propensity to aggregate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptides were primarily selected on the basis of predicted relatively higher blood brain barrier score, lower haemolytic activity and toxicity (Table 1). Among amphipathic peptides, we selected well-characterized and widely used pVEC, ARF, MAP and TP-10 while TAT, R8, IMT-P8, SynB3 and Penetratin were selected from the cationic class (Stalmans et al, 2015; Zhang et al, 2021). Peptides from the hydrophobic class were not selected due to their limited solubility and high propensity to aggregate.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the identification of suitable inhibitors of α-syn fibrillation has primarily been carried out by screening large libraries of small molecules. Attempts have been made to further enhance the efficacy of inhibitors by increasing their ability to cross the blood-brain barrier using approaches based on nanoparticles or cell-penetrating peptides (CPPs) (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results are very promising and demonstrate the therapeutic potentials of the CPP-modified nanomaterials on targeting brain diseases effectively. [160] These findings suggested that manipulating CPPs on NP surfaces would be a safe, effective, and promising strategy to improve IN medication transport for therapeutic applications in brain diseases. [161] Among all, the Bom/PEG-PCLTat is more effective to release camptothecin in the brain for GBM therapy via IN delivery, owing to the higher drug encapsulation efficiency (70%) and a more controllable drug release capacity.…”
Section: Cpp-modified Npsmentioning
confidence: 99%
“…The results are very promising and demonstrate the therapeutic potentials of the CPP‐modified nanomaterials on targeting brain diseases effectively. [ 160 ] These findings suggested that manipulating CPPs on NP surfaces would be a safe, effective, and promising strategy to improve IN medication transport for therapeutic applications in brain diseases. [ 161 ]…”
Section: Therapeutic Applications Of Modified Nps For Brain Diseasesmentioning
confidence: 99%
“…That study supported further development of therapeutic delivery platforms that enable compounds to more readily cross the BBB. Along these lines, cell‐penetrating peptides or peptides loaded onto nanoparticles have been in development to deliver therapeutic agents and proteins into the CNS (Zhang et al, 2021). Although this strategy is promising, the nanomaterials show signs of toxicity, and the delivery system itself lacks cell specificity.…”
Section: Therapeutic Interventions In Neurodegenerative Disease Progr...mentioning
confidence: 99%